tìm x,y,z biết:
x-2x+22x-23x+...+22018x-22019x=22020x-1
Giải các PT sau
1. \(\cos^2\left(x-30^{\cdot}\right)-\sin^2\left(x-30^{\cdot}\right)=\sin\left(x+60^{\cdot}\right)\)
2. \(\sin^22x+\cos^23x=1\)
3. \(\sin x+\sin2x+\sin3x+\sin4x=0\)
4. \(\sin^2x+\sin^22x=\sin^23x\)
1.Pt \(\Leftrightarrow cos\left(2x-\dfrac{\pi}{3}\right)=sin\left(x+\dfrac{\pi}{3}\right)\)
\(\Leftrightarrow cos\left(2x-\dfrac{\pi}{3}\right)=cos\left(\dfrac{\pi}{6}-x\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-\dfrac{\pi}{3}=\dfrac{\pi}{6}-x+k2\pi\\2x-\dfrac{\pi}{3}=x-\dfrac{\pi}{6}+k2\pi\end{matrix}\right.\)\(\left(k\in Z\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{6}+\dfrac{k2\pi}{3}\\x=\dfrac{\pi}{6}+k2\pi\end{matrix}\right.\)\(\left(k\in Z\right)\)
\(\Rightarrow x=\dfrac{\pi}{6}+\dfrac{k2\pi}{3}\)\(\left(k\in Z\right)\)
2.\(sin^22x+cos^23x=1\)
\(\Leftrightarrow\dfrac{1-cos4x}{2}+\dfrac{1+cos6x}{2}=1\)
\(\Leftrightarrow cos6x=cos4x\)
\(\Leftrightarrow\left[{}\begin{matrix}x=k\pi\\x=\dfrac{k\pi}{5}\end{matrix}\right.\)\(\left(k\in Z\right)\)\(\Rightarrow x=\dfrac{k\pi}{5}\)\(\left(k\in Z\right)\) (Gộp nghiệm)
Vậy...
3. \(Pt\Leftrightarrow\left(sinx+sin3x\right)+\left(sin2x+sin4x\right)=0\)
\(\Leftrightarrow2.sin2x.cosx+2.sin3x.cosx=0\)
\(\Leftrightarrow2cosx\left(sin2x+sin3x\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cosx=0\\sin3x=-sin2x\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{2}+k\pi\\sin3x=sin\left(\pi+2x\right)\end{matrix}\right.\)(\(k\in Z\))
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{2}+k\pi\\x=\pi+k2\pi\\x=\dfrac{k2\pi}{5}\end{matrix}\right.\)(\(k\in Z\))\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{2}+k\pi\\x=\dfrac{k2\pi}{5}\end{matrix}\right.\) (\(k\in Z\))
Vậy...
4. Pt\(\Leftrightarrow\dfrac{1-cos2x}{2}+\dfrac{1-cos4x}{2}=\dfrac{1-cos6x}{2}\)
\(\Leftrightarrow cos2x+cos4x=1+cos6x\)
\(\Leftrightarrow2cos3x.cosx=2cos^23x\)
\(\Leftrightarrow\left[{}\begin{matrix}cos3x=0\\cosx=cos3x\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{6}+\dfrac{k\pi}{3}\\x=-k\pi\\x=\dfrac{k\pi}{2}\end{matrix}\right.\)\(\left(k\in Z\right)\)\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{\pi}{6}+\dfrac{k\pi}{3}\\x=\dfrac{k\pi}{2}\end{matrix}\right.\)\(\left(k\in Z\right)\)
Vậy...
Giải phương trình:
a) \(Sin^22x+Cos^23x=0\)
b) \(Sin\left(x+\frac{\pi}{3}\right)Cos\left(x-\frac{\pi}{6}\right)=1\)
c) \(Cos^2x+Cos^22x+Cos^23x=1\)
giải pt
a, \(\sin^2x+\sin^22x+\sin^23x=\dfrac{3}{2}\)
b. \(\cos^2x+\sin^22x+\cos^23x=1\)
c,\(\sin5x+2\cos^2x=1\)
d,\(1+\tan x=2\sqrt{2}\sin\left(x+\dfrac{\pi}{4}\right)\)
e,\(\sin3x+\cos3x-\sin x+\cos x=\sqrt{2}\cos2x\)
1) Tìm x :
a) 5x3 + 3x2 + 3x + 1 = -23x
2) Tính giá trị của các biểu thức :
a) 2x3( x-y ) + 2x3( y-z ) + 2x3( z-x ) tại x = 1999 , y = 2016 , z = -2015
tìm x,y,z
(-5)^x / 125 = -25
|3x-1| = 7
(x + 1/4) (2x- 1/3) = 0
3x=y, 5y=4z, 23x-7y-2z= -4^4
\(\cos^2x+cos^22x+cos^23x+cos^24x=1\)
Tìm x,y,z biết: 3x=y; 5y=4z và 23x - 7y - 2z= -44
Ta có \(\hept{\begin{cases}3x=y\\5y=4z\end{cases}}\Rightarrow\hept{\begin{cases}\frac{x}{1}=\frac{y}{3}\\\frac{y}{4}=\frac{z}{5}\end{cases}}\Rightarrow\hept{\begin{cases}\frac{x}{4}=\frac{y}{12}\\\frac{y}{12}=\frac{z}{15}\end{cases}}\Rightarrow\frac{x}{4}=\frac{y}{12}=\frac{z}{15}\)
Đặt \(\frac{x}{4}=\frac{y}{12}=\frac{z}{15}=k\Rightarrow\hept{\begin{cases}x=4k\\y=12k\\z=15k\end{cases}}\)
Khi đó 23x - 7y - 2z = - 44
<=> 23.4k - 7.12k - 2.15k = -44
=> 92k - 84k - 30k = -44
=> -22k = -44
=> k = 2
=> x = 8 ; y = 24 ; z = 30
Tìm x,y biết:
a) 3 4 x + 1 5 = 1 6 b) 1 3 + 1 2 : x = − 4 c) c ) x − 2 3 x + 1 4 = 0
d) 2 x − 3 3 4 x + 1 = 0 d) 2 3 x + 1 2 − 5 3 = 0 e) 2 x − 0 , 3 = 1 , 5
f) x . − 3 5 3 = − 3 5 5 g) x : 1 3 2 = 1 3 3 h) x 26 = 21 39
k) 1 3 x = 2 3 1 6 l) 77 7 9 5 9 = x 0 , 03 m) 2 2 3 0 , 03 = 1 7 9 x
n) 2 x − 3 2 = 16 o) 3 x − 2 5 = − 243
1)\(sin^23x.cos2x+sin^2x=0\)
2)
\(cos^23x+cos^22x=sin^2x\)
3)
\(\frac{1}{4}+cos^2\frac{x}{3}=\frac{1}{2}sin^2\frac{x}{2}\)
4)
\(sin^23x-sin^22x-sin^2x=0\)
5)
\(2cos^2x=3sin^25x+2\)
6) 3cosx+2cos2x-cos3x=2sinxsin2x-1
7) \(sinx+cosx=\sqrt{2}\left(2-sin^32x\right)\)
1.
\(\Leftrightarrow\left(1-cos6x\right)cos2x+1-cos2x=0\)
\(\Leftrightarrow cos2x-cos2x.cos6x+1-cos2x=0\)
\(\Leftrightarrow\frac{1}{2}\left(cos8x-cos4x\right)-1=0\)
\(\Leftrightarrow2cos^24x-cos4x-3=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos4x=-1\\cos4x=\frac{3}{2}\left(l\right)\end{matrix}\right.\)
\(\Leftrightarrow4x=\pi+k2\pi\)
\(\Leftrightarrow x=\frac{\pi}{4}+\frac{k\pi}{2}\)
2.
\(\Leftrightarrow1+cos6x+2cos^22x=1-cos2x\)
\(\Leftrightarrow cos6x+cos2x+2cos^22x=0\)
\(\Leftrightarrow cos4x.cos2x+cos^22x=0\)
\(\Leftrightarrow cos2x\left(cos4x+cos2x\right)=0\)
\(\Leftrightarrow cos2x\left(2cos^22x+cos2x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos2x=0\\cos2x=-1\\cos2x=\frac{1}{2}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{\pi}{4}+\frac{k\pi}{2}\\x=\frac{\pi}{2}+k\pi\\x=\pm\frac{\pi}{6}+k\pi\end{matrix}\right.\)
3.
Đặt \(\frac{x}{6}=t\Rightarrow\frac{1}{4}+cos^22t=\frac{1}{2}sin^23t\)
\(\Leftrightarrow1+4cos^22t=1-cos6t\)
\(\Leftrightarrow cos6t+4cos^22t=0\)
\(\Leftrightarrow4cos^32t+4cos^22t-3cos2t=0\)
\(\Leftrightarrow cos2t\left(4cos^22t+4cos2t-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos2t=0\\cos2t=\frac{1}{2}\\cos2t=-\frac{3}{2}\left(l\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}t=\frac{\pi}{4}+\frac{k\pi}{2}\\t=\pm\frac{\pi}{6}+k\pi\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{x}{3}=\frac{\pi}{4}+\frac{k\pi}{2}\\\frac{x}{3}=\frac{\pi}{6}+k\pi\\\frac{x}{3}=-\frac{\pi}{6}+k\pi\end{matrix}\right.\)
\(\Leftrightarrow x=...\)
Hàng Đẳng Thức
a) 3^3+9x^2-6x
b)8x^2-22x-7
c)8x^2+2x^2+5
d) 4x^4-x^2
e) 6x^2-7x-5
f)-4x^2+23x-15
d) \(4x^4-x^2=x^2\left(4x^2-1\right)=x^2\left(2x-1\right)\left(2x+1\right)\)
e) Ta có: \(6x^2-7x-5\)
\(=6x^2-10x+3x-5\)
\(=2x\left(3x-5\right)+\left(3x-5\right)\)
\(=\left(3x-5\right)\left(2x+1\right)\)
f: Ta có: \(-4x^2+23x-15\)
\(=-4x^2+20x+3x-15\)
\(=-4x\left(x-5\right)+3\left(x-5\right)\)
\(=\left(x-5\right)\left(-4x+3\right)\)